2010
DOI: 10.1007/s12272-010-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of artemether solid dispersions with hydrophilic carriers by freeze dried and melt methods

Abstract: Solid dispersions of artemether (ARM), a poorly soluble drug, were prepared using polyvinylpyrrolidone (PVPK25, MW 25000) and polyethyleneglycol (PEG4000, MW 4000) as excipients. These dispersions were studied by physical mixture, freeze-drying, and melting methods. They were characterized by X-ray diffraction pattern, fourier transform infrared spectrophotometry, differential scanning calorimetery, and dissolution studies. X-ray diffraction pattern revealed the complete crystalline nature of artemether, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…These results indicated that one hydrogen bond formed between the free O—H of the AZ and PEG (red shifting) while the second hydrogen bond between a water molecule and AZ was disrupted (blue shifting). These results are consistent with previous data (Ansari et al, 2010) and supported the results of X-ray diffraction.…”
Section: Resultssupporting
confidence: 94%
“…These results indicated that one hydrogen bond formed between the free O—H of the AZ and PEG (red shifting) while the second hydrogen bond between a water molecule and AZ was disrupted (blue shifting). These results are consistent with previous data (Ansari et al, 2010) and supported the results of X-ray diffraction.…”
Section: Resultssupporting
confidence: 94%
“…The literature has shown that higher glass transition temperature and higher viscosity of polymers usually show superior stability for the amorphous drug [9]. The specific interactions between drug and polymer are important considerations for stabilization of the amorphous formulation [10]. Therefore the evaluation and selection of polymer are key factors in developing solid dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is polyvinylpyrrolidone (PVP), a vehicle often employed due to its low toxicity, high aqueous solubility and physiological tolerance (Marin et al, 2002;Narang and Srivastava, 2002). Studies on PVPassociated solid dispersions of pharmaceuticals have revealed inhibited crystallization and enhanced solubility; examples include bicalutamide (Andrews et al, 2010), AM (Ansari et al, 2010), piroxicam (Wu et al, 2009), DHA (Ansari and Sunderland, 2008), lamotrigine (Shinde et al, 2008), valdecoxib (Ambike et al, 2004), carbamazepine (Sethia andSquillante, 2004), artemisinin (Nijlen et al, 2003), camptothecin (Kang et al, 2002). Similar studies reported increased bioavailability of ketoconazole (Heo et al, 2005), artemisinin (Wong and Yuen, 2001), norfloxacin (Fawaz et al, 1996), lonidamine (Palmieri et al, 2002) and nifedipine (Emara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%